Development and Psychometric Testing of the Self-Management Difficulty Scale for Pregnant Nurses - Hino, Marie; Ebina, Yasuhiko; Yano, Rika (Pacific Rim International Journal of Nursing Research, 2025)
Pregnant nurses are at high risk of perinatal abnormalities due to occupational hazards and face difficulties in performing appropriate self-management. To facilitate self-management among pregnant nurses, it is necessary to assess their difficulties. This study aimed to develop a Self-Management Difficulty Scale to measure self-management difficulties of pregnant nurses and evaluate its psychometric properties. The scale was developed in three phases: Phase I involved drafting the scale through literature reviews, panel discussions with experts, and pre-testing with pregnant nurses, resulting in 41 draft items that constituted self-management difficulties. In Phase II, a preliminary survey was conducted with 232 nurses from four hospitals in two Japanese cities to validate these items. Item and exploratory factor analysis were performed, and 28 items remained. In Phase III, a psychometric test was conducted with 172 pregnant nurses from 20 hospitals in 10 Japanese cities. Results of confirmatory factor analysis revealed that the 28-item Self-Management Difficulty Scale consisted of 4 subscales: ‘duelling roles of a nurse and a pregnant woman’, ‘prioritising the foetus’, ‘unsure about management’, and ‘perceiving one’s limits’, and good construct validity. Additionally, concurrent and convergent validity, as well as the adequate reliability of the total and subscales, were confirmed. In conclusion, the Self-Management Difficulty Scale has both accepted validity and reliability. It can be used for screening perinatal abnormality risk, early intervention, and promoting self-management behaviours. Further study is required to validate the construct validity by various types, known-group technique, and predictive validity of this scale in other populations of pregnant women.